Pengaruh Caregiver Burden Terhadap Psychological Well-Being Dimoderatori Oleh Resiliensi Pada Ibu Generasi Sandwich - Asy’syifa, Farah (Jurnal Syntax Fusion, 2023)
This study aims to determine the moderating effect of resilience on the relationship between caregiver burden and psychological well-being in mothers of the sandwich generation. Providing care for two generations simultaneously leads to a decrease in psychological well-being triggered by the caregiver burden experienced by mothers of the sandwich generation. The presence of resilience in individuals can enhance psychological well-being even when they are still experiencing caregiver burden. This quantitative study utilized a survey method with questionnaires, including the Burden Scale for Family Caregivers short scale, Ryff’s Psychological Well-Being Scale, and the Resilience Scale, which were administered to 130 Indonesian married housewives aged 30 to 55 years old, who were simultaneously taking care of and living with both their parents/in-laws and children. Data analysis was performed using moderator analysis techniques with the assistance of the statistical software Jamovi for Windows version 3.2.28. The results of the study indicate that caregiver burden has a negative impact on the psychological well-being of mothers in the sandwich generation. Furthermore, the resilience of mothers in the sandwich generation has a positive influence on psychological well-being, but resilience does not moderate the influence of caregiver burden and psychological well-being